Alur Penggunaan Media Sosial Instagram Naker_Jatim untuk Publikasi Program Ketenagakerjaan - Febrianti, Natasya Maura Amanda; Nafi’ah, Binti Azizatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In implementing the use of social media in the public sector as stated by Khan (2015), by utilizing social media, the government can share information with the public at the same time as also promoting public services, and empowering ordinary people in the form of designing self-service concepts in the future. The East Java Provincial Manpower and Transmigration Service is a Regional Organization (OPD) which is strategic in implementing the vision and mission of the East Java Provincial Government in the field of employment and has an important role in efforts to increase Manpower Utilization, Equal Employment Opportunities, Worker Protection and Welfare Workers, Efforts to Reduce Unemployment and Expand Information on the Transmigration Program of the East Java Provincial Government. This research looks at the problems at the preparation stage and the flow of obstacles in the implementation process of using the Instagram social media platform in the publication of employment programs. So the aim of this research is to find out the extent of the use of social media Instagram Naker_Jatim for the publication of employment programs. The method used in this research is a qualitative descriptive method. The informants in this research were the Publication Team of the East Java Province Manpower and Transmigration Service. Data collection techniques use interviews, observation and documentation. The research results showed that the implementation of digital publications via social media Instagram Naker_Jatim had not run optimally because of constraints in terms of human resources in the Publication Team of the East Java Province Manpower and Transmigration Service, whose numbers were smaller compared to the number of digital publication workloads.